Influence of Alkali Metal Oxide Slag Aggregating Agent on the Performance of Magnesium Desulfurization Slags - Wufeng JIANG; Liang TIAN; Suju HAO; He BO; Tengfei MA; Yuzhu ZHANG (Kuangchan zonghe liyong)
This is an article in the field of metallurgical engineering. In view of the thin slag layer in the desulfurization process of magnesium-based desulfurizers, it is difficult to remove cleanly, resulting in high-concentration desulfurization slag being brought into the converter, causing the problem of sulfur back in the converter. The liquidus diagram of CaO-SiO2-Al2O3-MgO(FeO) desulfurization slag was drawn by FactSage software, and the phase composition of desulfurization slag and the influence of desulfurization slag composition on the liquid phase area were analyzed, and the sensitivity of desulfurization slag to temperature was reduced, which is conducive to slag removal. A slag aggregation agent whose main component is SiO2 was designed to control the performance of desulfurization slag. The initial melting temperature, hemispherical point temperature and fluidity temperature of the desulfurization slag were measured by a melting point melt rate meter, and the effect of the addition amount of slag aggregation agent on the melting performance of the desulfurization slag was studied. The results show that when the ratio of desulfurization slag to slag aggregation agent is 5∶2～5∶5, the temperature difference between the initial melting temperature and the fluidity temperature of the desulfurization slag can be increased, and the thermal stability of the desulfurized slag can be improved. The ratio of acid desulfurization slag added to the slag aggregate agent should be low, and the desulfurization slag basicity can be increased appropriately to increase the slag aggregate agent ratio.